An Assessment of the National Institute of Standards and Technology Center for Nanoscale Science and Technology: Fiscal Year 2009 (National Academies Press, 2009)
The National Institute of Standards and Technology's (NIST's) Center for Nanoscale Science and Technology (CNST) was founded on May 1, 2007, and remains in development with respect to projects and staffing. It aspires to be recognized both as a world leader in each of its research areas and as an organization providing ready access to unexcelled nanoscale measurement and fabrication facilities. An Assessment of the National Institute of Standards and Technology Center for Nanoscale Science and Technology evaluates the overall CNST accomplishments and operations for FY 2009. As requested by the Deputy Director of NIST, the scope of the assessment included the following criteria: (1) the technical merit of the current laboratory programs relative to current state-of-the-art programs worldwide; (2) the adequacy of the laboratory budget, facilities, equipment, and human resources, as they affect the quality of the laboratory's technical programs; and (3) the degree to which the laboratory programs in measurement science and standards achieve their stated objectives and desired impact.